Life satisfaction in people affected by a severe psychiatric condition: a comprehensive model. Issue 1 (2nd January 2023) - Caballero, Rocío; Chaves, Covadonga; Valiente, Carmen
ABSTRACT: "Research on severe psychiatric conditions has primarily focused on deficits and symptoms, while there is limited understanding about the underlying factors that contribute to the life satisfaction (LS) of patients who suffer from such conditions. The presence of positive affect has an important role in the LS in the general population. Its presence activates personal resources that facilitate the achievement of their life purposes. However, these associations have not yet been evaluated in people affected by a severe psychiatric condition. The main aim of this study was to explore, using structural equation modeling, the role of different hedonic and eudaimonic well-being dimensions as predictors of LS in schizophrenia spectrum disorders. A total of 149 adult participants with schizophrenia spectrum disorders were assessed about their LS, hedonic well-being (i.e., positive affect, openness to the future) and eudaimonic well-being (i.e., social support, self-compassion, and strengths). Results indicate that self-compassion, caring and self-control strengths and social support mediate the relationship between hedonic well-being and LS. These findings help understand the mechanisms involved in LS in this population and shed light on the design of future interventions aimed at promoting a more satisfying life for them".